A detailed experimental and theoretical investigation of the role of cyano groups in the π-bridged acceptor of sensitizers for use in dye-sensitized solar cells (DSCs). Issue 42 (23rd October 2017) - Xu, Qinqin; Yang, Guang; Ren, Yu; Lu, Futai; Zhang, Nuonuo; Qamar, Muhammad; Yang, Manlin; Zhang, Bao; Feng, Yaqing
Abstract : Porphyrin sensitizersLX1, LX2 andLX3 were synthesized for use in DSCs and their electronic properties with TiO2 were investigated in detail using theoretical calculations. Abstract : Three donor–π conjugated unit–acceptor (D–π–A) type zinc porphyrin sensitizersLX1, LX2 andLX3 bearing meso acrylic acid, α-cyanoacrylic acid, and α-cyanopentadienoic acid, respectively, as the π-bridged acceptors were designed and synthesized for use in dye-sensitized solar cells (DSCs). The interesting role of the cyano group attached to the α position of the acrylic and pentadienoic acid acceptor was investigated. It was shown that even though the introduction of the cyano group and the elongation of the π-bridge can both increase the light-harvesting as indicated by the UV-vis absorption spectra, the relevant cell performance dropped significantly. The photo to power conversion efficiencies (PCEs) of the devices increase in the order ofLX1 >LX2 >LX3, with the highest PCE of 6.04% achieved for theLX1 -based cell, which bears acrylic acid as the π-bridged acceptor. To further explore the effect of –CN and –CHCH– on the interaction between the absorbed dye and TiO2 substrates, their density of states (DOS) and partial density of states (PDOS), as well as electronic properties were investigated in detail using theoretical calculations. The results suggest that introducing the –CN group into the acceptor and extending the conjugation of the π-bridge have decreased the LUMO levels of the dyes, leading to weak interfacial coupling, low electron injection driving force, low J sc, and thus poor cell performance.